Surface functionalization of starch/polycaprolactone fiber meshes for bone guide regeneration - López-Pérez, P. M. (2008)
[Excerpt] Surface design of biomedical devices is crucial for their acceptation or rejection by the body. One of the most versatile and effective tools to tailor surface chemistry and properties of solids is polymer grafting. This work describes the modification of starch/polycaprolactone scaffolds by surface grafting of sulfonic and phosphonic groups and the effect of those groups on osteoblast-like cells behaviour on a preliminary base. [...]